2020
DOI: 10.30629/2658-7947-2020-25-5-36-44
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensity in middle-age adults (40–59 years) and risk factors for cerebrovascular disease

Abstract: Introduction. White matter hyperintensity (WMH) is a neuroimaging age-related phenomenon associated with an increased cardiovascular risk in people with arterial hypertension (AH). The prevalence of WMH and its relationship with risk factors for cerebrovascular disease (CVD) in middle-age population requires clarification. Aim: to assess the prevalence of the WMH phenomenon in people of working age (40–59 years) and to establish cerebrovascular risk factors associated with its development. Material and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…When viewed in terms of the middle-aged group, this age group has a high prevalence of several diseases, such as cardiovascular disease, arterial HT, DM, and hyperlipidemia, which are comorbidities of stroke. 4,25,26 The increased risk of HT in patients with periodontitis is 81%. Periodontitis induces a systemic inflammatory process that directly results in HT due to decreased vasodilatory function.…”
Section: Discussionmentioning
confidence: 99%
“…When viewed in terms of the middle-aged group, this age group has a high prevalence of several diseases, such as cardiovascular disease, arterial HT, DM, and hyperlipidemia, which are comorbidities of stroke. 4,25,26 The increased risk of HT in patients with periodontitis is 81%. Periodontitis induces a systemic inflammatory process that directly results in HT due to decreased vasodilatory function.…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned two studies indirectly suggested that oral inflammatory diseases such as PD may promote the occurrence, development, and recurrence of atrial fibrillation. Holm-Pedersen [13] et al found that patients with one to two active coronal caries lesions had 2.8 times higher odds (95% CI 1.1-7.0) of arrhythmia than those without active coronal caries, but there was no association between arrhythmia and periodontal disease. And this study did not further analyze the relationship between active coronal caries, periodontitis, and atrial fibrillation.…”
Section: Relationship Between Pd Oral Inflammatory Diseases and Atria...mentioning
confidence: 99%